Noodweer Exces in Self-Defense Perspective Positive Criminal Law and Islamic Criminal Law - Fauzi, Muhammad; Zuhri, Ahmad (LEGAL BRIEF, 2025)
The increase in criminal acts occurring nowadays has led some victims of crime to defend themselves when attacked by the perpetrators. Self-defense that has been carried out by someone sometimes exceeds the limits of what should be done. In this case, the perpetrator of self-defense is referred to as the crime of noodweer exces. The above issue makes the author want to examine and discuss the laws and sanctions for the perpetrators of noodweer exces. In this research, the author uses the normative legal research method with data collection techniques, namely library research, where the author examines and analyzes legal books, fiqh, the Criminal Code, and hadith. From the results of the research conducted, the author concludes that perpetrators of the crime of noodweer exces, according to the perspective of positive criminal law, cannot be punished, in accordance with the provisions of Article 49 paragraph (2). Meanwhile, in the perspective of Islamic criminal law, every perpetrator of the crime of noodweer exces will be subjected to qishas or may pay the specified diyat